Antibacterial activity of a stearic acid derivative from Stemodia foliosa - Dantas Da Silva, Lourinalda Luiza [UNESP]; Nascimento, Márcia; Siqueira Silva, Dulce Helena [UNESP]; Furlan, Maysa [UNESP]; Bolzani, Vanderlan da Silva [UNESP] (Thieme, 2002)
From the hexane-soluble fraction of an ethanol extract from leaves and stems of Stemodia foliosa (Scrophulariaceae), the new stearic acid 4-[(n-pentoxy)phenethyl] ester (1) was isolated. This compound exhibited antibacterial properties at 10μg/mL concentration by using disc diffusion method against Gram-positive bacteria Bacillus cereus and Bacillus subtilis and fast-acid bacterium Mycobacterium fortuitum. The structure of the new compound was elucidated by spectroscopic methods and by chemical conversion.
Keywords: 4 [(n pentoxy)phenethyl] ester; alcohol; clarithromycin; ester; hexane; plant extract; stearic acid derivative; unclassified drug; acid fast bacterium; antibacterial activity; Bacillus subtilis; controlled study; Gram positive bacterium; Mycobacterium fortuitum; nuclear magnetic resonance spectroscopy; plant leaf; plant stem; Scrophulariaceae; Anti-Bacterial Agents; Bacteria; Clarithromycin; Magnetic Resonance Spectroscopy; Molecular Structure; Plant Extracts; Plant Leaves; Plant Stems; Stearates; Stearic Acids; Actinobacteria (class); Bacillus cereus; Bacteria (microorganisms); Mycobacterium; Posibacteria; Stemodia; uncultured actinomycete